A new HIF‐1α/RANTES‐driven pathway to hepatocellular carcinoma mediated by germline haploinsufficiency of SART1/HAF in mice. Issue 5 (7th March 2016) - Koh, Mei Yee; Gagea, Mihai; Sargis, Timothy; Lemos, Robert; Grandjean, Geoffrey; Charbono, Adriana; Bekiaris, Vasileos; Sedy, John; Kiriakova, Galina; Liu, Xiuping; Roberts, Lewis R.; Ware, Carl; et al.
Abstract : The hypoxia‐inducible factor (HIF), HIF‐1, is a central regulator of the response to low oxygen or inflammatory stress and plays an essential role in survival and function of immune cells. However, the mechanisms regulating nonhypoxic induction of HIF‐1 remain unclear. Here, we assess the impact of germline heterozygosity of a novel, oxygen‐independent ubiquitin ligase for HIF‐1α: hypoxia‐associated factor (HAF; encoded by SART1 ). SART1 −/− mice were embryonic lethal, whereas male SART1 +/− mice spontaneously recapitulated key features of nonalcoholic steatohepatitis (NASH)‐driven hepatocellular carcinoma (HCC), including steatosis, fibrosis, and inflammatory cytokine production. Male, but not female, SART1 +/− mice showed significant up‐regulation of HIF‐1α in circulating and liver‐infiltrating immune cells, but not in hepatocytes, before development of malignancy. Additionally, Kupffer cells derived from male, but not female, SART1 +/− mice produced increased levels of the HIF‐1‐dependent chemokine, regulated on activation, normal T‐cell expressed and secreted (RANTES), compared to wild type. This was associated with increased liver‐neutrophilic infiltration, whereas infiltration of lymphocytes and macrophages were not significantly different. Neutralization of circulating RANTES decreased liver neutrophilic infiltration and attenuated HCC tumor initiation/growth in SART1 +/− mice. Conclusion : This work establishes a new tumor‐suppressor role for HAF in immune cell function by preventing inappropriate HIF‐1 activation in male mice and identifies RANTES as a novel therapeutic target for NASH and NASH‐driven HCC. (Hepatology 2016;63:1576‐1591)